2019
DOI: 10.1111/apt.15240
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sustained virological response to direct‐acting anti‐viral therapy on the risk of extrahepatic manifestations of hepatitis C infection

Abstract: Background: Direct-acting anti-viral (DAA) therapy may have a beneficial role in extrahepatic manifestations of hepatitis C virus (HCV) infection. However, the available data are limited. Aim: To examine the effects of DAA treatment on the risk of several extrahepatic manifestations of HCV. Methods: We conducted a retrospective cohort study of patients from the US Department of Veterans Affairs Corporate Data Warehouse who had a positive HCV RNA test and received first course of DAAs between 2012 and 2016. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 27 publications
0
39
1
Order By: Relevance
“…56 A retrospective cohort study has shown that the risk of non-Hodgkin lymphoma was not significantly reduced after DAA-induced SVR (hazard ratio, 0.86; 95% confidence interval, 0.52-1.43) after only 2.01 years of follow-up. 56 HCV eradication may reduce the risk of vascular events. 57 However, this was not always the case.…”
Section: Extrahepatic Manifestationsmentioning
confidence: 99%
“…56 A retrospective cohort study has shown that the risk of non-Hodgkin lymphoma was not significantly reduced after DAA-induced SVR (hazard ratio, 0.86; 95% confidence interval, 0.52-1.43) after only 2.01 years of follow-up. 56 HCV eradication may reduce the risk of vascular events. 57 However, this was not always the case.…”
Section: Extrahepatic Manifestationsmentioning
confidence: 99%
“…Well‐controlled concomitant diseases by pharmacologic treatment are important, not only for diseases control but also for improving outcomes of associated diseases. For CHC patients with NAFLD, clearance of HCV offers benefits on reducing hepatic and extrahepatic events . A previous study showed that steatosis is a negative predictor of SVR following interferon treatment .…”
Section: Chronic Hepatitis Viral Infection and Fatty Livermentioning
confidence: 99%
“…Moreover, SVR achievement was associated with reduced insulin resistance at follow‐up and a protective effect on the incidence of diabetes 37 . El‐Serag et al reported that successful DAA treatment resulting in SVR was associated with significant reductions in the future risk of conditions, including mixed cryoglobulinemia, glomerulonephritis, and lichen planus 39 …”
Section: Discussionmentioning
confidence: 99%